2020
DOI: 10.3389/feduc.2020.586123
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Diaries: Identity, Teaching, and Learning at a Crossroads

Abstract: Despite the fact that American education has at its core strived to provide pathways of opportunity to remedy socio-economic inequalities, as educational institutions transitioned into online virtual classrooms due to the COVID-19 pandemic these inequalities have come into sharper focus for us. During the process of engaging in a larger self-study, we became more aware of the stark socio-economic disparities of our students in a virtual space, specifically amongst students of color, and how these disparities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
10
0
2
Order By: Relevance
“…We were aware that employing a research design that involved the recruitment of large numbers of participants may slow the research process, and in doing so prevent us from accessing data on the immediate perspectives and concerns of teachers during the first few weeks of the lockdown in England. Our study, which collected rich qualitative data from a small sample, was aligned with a number of other small-scale educational studies conducted during the early stages of the Covid-19 crisis (Anderson et al, 2020 ; Kim and Asbury, 2020 ; Sequeira and Dacey, 2020 ; Ferguson et al, 2021 ).…”
Section: Methodsmentioning
confidence: 72%
See 1 more Smart Citation
“…We were aware that employing a research design that involved the recruitment of large numbers of participants may slow the research process, and in doing so prevent us from accessing data on the immediate perspectives and concerns of teachers during the first few weeks of the lockdown in England. Our study, which collected rich qualitative data from a small sample, was aligned with a number of other small-scale educational studies conducted during the early stages of the Covid-19 crisis (Anderson et al, 2020 ; Kim and Asbury, 2020 ; Sequeira and Dacey, 2020 ; Ferguson et al, 2021 ).…”
Section: Methodsmentioning
confidence: 72%
“…Corpus linguistic analysis of data is facilitated through specialized computer programs. In this project, analysis of pronoun use within the interview data was undertaken using Wordsmith 7.0 (Scott, 2016), which facilitated the construction of wordlists (frequency counts of words within a specific corpus) and concordances (which show all the occurrences of a target word within their context, to reveal linguistic patterns and associations). Corpus linguistics is a comparatively "young discipline that is [.…”
Section: Discussionmentioning
confidence: 99%
“…No obstante, con el paso del tiempo se está acrecentando paulatinamente la bibliografía sobre la pandemia surgida de la investigación social empírica. En este sentido, contamos ya con un buen número de estudios que se han centrado en analizar cómo las transformaciones sociales generadas por la pandemia han afectado emocionalmente a los estudiantes universitarios en distintos lugares del mundo: Europa (Burns et al, 2020;Caparrós Martín, et al, 2021;Csillag & Hidegh, 2020;Lozano-Díaz, Fernández-Prados, et al, 2020), América Latina (Hernández Ferrer & Valencia Aguilar, 2021;Gandulfo, Alegre, & Domínguez, 2020;Reyes & Trujillo, 2021) y Estados Unidos (Sequeira & Dacey, 2020), entre otros. Destaca, en este sentido, el estudio realizado por Aristovnik y sus colaboradores (2020) a partir de una encuesta aplicada a una muestra de más de 30000 estudiantes, de 62 países distintos, donde se subraya como ciertas variables sociodemográficas y geopolíticas afectan a las distintas emociones expresadas por los estudiantes y a sus formas de lidiar con la incertidumbre generada por la pandemia.…”
Section: La Pandemia De La Covid-19 Y El Confinamiento En Los Diarios...unclassified
“…Researchers revealed that student motivation and engagement tended to decrease after the sudden transition to ERT (Aguilera-Hermida, 2020). Students, disproportionately those from the lower end of the socioeconomic spectrum, did not feel comfortable participating in live activities and failed to show up regularly in virtual classrooms (Sequeira & Dacey, 2020). Some students found it difficult to fully engage during quarantine due to a lack of sufficient study space and constant distractions (Qadir, 2020).…”
Section: Motivation and Engagementmentioning
confidence: 99%
“…On the other hand, although digital equipment and internet access did not constitute a sizable barrier for US college students, its reliability and stability nevertheless hampered a part of the population (Katz et al, 2021). Additionally, underprivileged and vulnerable students lost motivation due to technological constraints, a lack of supporting facilities, and poor digital skills (Sequeira & Dacey, 2020). These findings underscore the existing disparities in access to support and opportunities during ERT and the importance of implementing more caring pedagogical approaches to learn about and empower learners (Sequeira & Dacey, 2020).…”
Section: Equity and Inclusionmentioning
confidence: 99%